Evaluation of the main pharmacies used for the sars-cov-2: a scientific and technological prospection (Research, Society and Development, 2021)
Coronaviruses are viruses that cause respiratory infections that can affect animals and humans. The SARS-CoV-2 epidemic, which caused COVID-19, began in Wuhan (China) in December 2019, and spread to several countries, becoming a dangerous pandemic without specific treatment. This work aims to show cases treated with the main drugs for SARS-CoV-2, evaluating its efficacy and disadvantages. Publications with data from pharmacological treatments for the new SARS-CoV-2, scientific publications, world health organization (WHO) and governmental publications were used, among the date (2019-2020). Data were collected from the following scientific databases: LILACS, PUBMED, PERIODICOS, GOOGLE ACADEMICOS, SCIENCE DIRECT, BIRAME, Virtual Health Library - VHL, SCIELO, Cochrane Library, HighWire Press, Scopus and Elsevier; and the technological bases: WIPO and PTO. The use of these drugs may have led to improvement and cure of patients globally. They are believed to be effective against the disease. However, we need scientific proofs. In the results we observed the drugs used worldwide and the patents approved until (15/09/2020). There is no treatment for Covid19, medications that soften the flu-like symptoms of the disease were used. In emergency cases, the combination of the antibiotic azithromycin and hydroxychloroquine, used for malaria and other medicines, was used. This study evaluated most of the drugs that are in use for the treatment of SARS-CoV-2, in order to present a drug or more that is effective for the treatment of the disease, also showing whether in vitro and in vivo research was conducted in the search for a better treatment.